Perinatal mortality and neonatal and maternal outcome per gestational week in term pregnancies: A registry‐based study - Jérôme Cornette; Catharina J. van derStok; Irwin K. M. Reiss; René F. Kornelisse; Eline van derWilk; Arie Franx; Yves Jacquemyn; Eric A. P. Steegers; Loes C. M. Bertens (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Human pregnancy is considered term from 37+0/7 to 41+6/7 weeks. Within this range, both maternal, fetal and neonatal risks may vary considerably. This study investigates how gestational age per week is related to the components of perinatal mortality and parameters of adverse neonatal and maternal outcome at term. Material and Methods A registry‐based study was made of all singleton term pregnancies in the Netherlands from January 2014 to December 2017. Stillbirth and early neonatal mortality, as components of perinatal mortality, were defined as primary outcomes; adverse neonatal and maternal events as secondary outcomes. Neonatal adverse outcomes included birth trauma, 5‐minute Apgar score ≤3, asphyxia, respiratory insufficiency, neonatal intensive care unit admission and composite neonatal outcome. Maternal adverse outcomes included instrumental vaginal birth, emergency cesarean section, obstetric anal sphincter injury, postpartum hemorrhage, hypertensive disorders of pregnancy and composite maternal outcome. The primary outcomes were evaluated by comparing weekly prospective risks of stillbirth and neonatal death using a fetuses‐at‐risk approach. Secondly, odds ratios (OR) for perinatal mortality, adverse neonatal and maternal outcome using a births‐based approach were compared for each gestational week with all births occurring after that week. Results Data of 581 443 births were analyzed. At 37, 38, 39, 40, 41 and 42 weeks, the respective weekly prospective risks of stillbirth were 0.015%, 0.022%, 0.031%, 0.036%, 0.069% and 0.081%; the respective weekly prospective risks of early neonatal death were 0.051%, 0.047%, 0.032%, 0.031%, 0.039% and 0.035%. The OR for adverse neonatal outcomes were the lowest at 39 and 40 weeks. The OR for adverse maternal outcomes, including operative birth, continuously increased with each gestational week. Conclusions The prospective risk of early neonatal death for babies born at 39 weeks is lower than the risk of stillbirth in pregnancies continuing beyond 39+6/7 weeks. Birth at 39 weeks was associated with the best combined neonatal and maternal outcome, fewer operative births and fewer maternal and neonatal adverse outcomes compared with pregnancies continuing beyond 39 weeks. This information with appropriate perspectives should be included when counseling term pregnant women.